PCAOB guidance and audits of fair values for Level 2 investments - Emett, Scott A.; Libby, Robert; Nelson, Mark W. (Accounting, Organizations and Society, 2018)
Investments that are classified as Level 2 within the fair value hierarchy account for approximately 92 percent of US banks' fair value assets. We report an experiment that examines how experienced auditors apply current PCAOB guidance when auditing portfolios of these assets. We hypothesize and find that, depending on how overstatement is distributed within a portfolio, current PCAOB guidance leads auditors to make adjustments that are predictably larger or smaller than the aggregate overstatement in the portfolio. Auditors are more likely to follow PCAOB guidance when doing so leads to lower audit adjustments and higher client income. We also predict and find that auditors identify some patterns of overstatement as indicative of management bias, but not others. However, management-bias assessments do not affect auditors' adjustment decisions as standards imply they should, even when auditors are prompted to consider management bias. Together, these results highlight a potential deficiency in current auditing guidance that managers could exploit by strategically locating overstatements within securities with larger book values or by spreading those overstatements across many securities within a portfolio. We suggest changes to current PCAOB guidance which may reduce these effects.